The evaluation of the effect of Helicobacter pylori infection on choroidal thickness - Üçgül Atılgan, Cemile; Yozgat, Ahmet; Kösekahya, Pınar; Çağlayan, Mehtap; Şendul, Selam Yekta; Berker, Nilüfer; Altıparmak, Zeynep; Altıparmak, Emin; Yılmazbaş, Pelin (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: To evaluate the effects of Helicobacter pylori infection on choroidal thickness (CT) using enhanced depth imaging spectral domain-optical coherence tomography (SD-OCT). Materials and Methods: A total of 63 right eyes of 63 patients who tested positive for H. pylori (Group 1) and 46 right eyes of 46 patients who tested negative for H. pylori (Group 2) were evaluated. The CTs at the subfoveal area and at 1 mm ranging up to 3 mm from the fovea at the nasal and temporal quadrants were measured and compared. After the eradication of H. pylori, the CT values were also compared with the pre-eradication values in 38 patients. Results: The mean age of patients was 43.6±9.5 years in Group 1 and 46.6±11.5 years in Group 2 (p=0.13). Differences in CT values between Groups 1 and 2 before and after H. pylori eradication were not statistically significant (p>0.05 for all values). Conclusion: The CT values of H. pylori positive and H. pylori negative patients were similar. Eradication of H. pylori infection appears to have produced no change in short-term CT. Cite this article as: Üçgül Atılgan C, Yozgat A, Kösekahya P, et al. The evaluation of the effect of Helicobacter pylori infection on choroidal thickness. Turk J Gastroenterol 2018; 29: 636-41.